Six new Thesium (Santalaceae) species endemic to the Greater Cape Floristic Region, South Africa, and one new name - Zhigila, Daniel Andrawus; Verboom, G. Anthony; Stirton, Charles H.; Smith, Harry J.; Muasya, A. Muthama (Phytotaxa, 2019)
Six new species of Thesium endemic to the Greater Cape Floristic Region (GCFR) of South Africa are described and illustrated. These are Thesium aspermontanum, T. dmmagiae, T. neoprostratum, T. nigroperianthum, T. rhizomatum, and T. stirtonii. In addition, Thesium assimile var. pallidum is elevated to species rank as T. sawae. Morphological and ecological differences of each species, along with their putative affinities, preliminary conservation status, phenology, etymology, and distributional maps are presented.